2007
DOI: 10.1080/09546630701395044
|View full text |Cite
|
Sign up to set email alerts
|

The effect of topical corticosteroids in combination with alefacept on circulating T‐cell subsets in psoriasis

Abstract: Alefacept selectively targets the CD45RO+ lymphocyte population, as well as some other subpopulations of lymphocytes. This effect is independent of the use of additional topical therapy during the first 4 weeks. The extent of the decrease, on the contrary, is dependent on the use of corticosteroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Economidou et al found increased baseline CD3+CD25+ T cells and a reduction in CD25 expression after treatment with cyclosporine [17]. Similarly, Langewouters et al demonstrated a significant decrease in CD4+CD25+ T cells soon after the introduction of treatment with afefacept [18]. Reddy et al evaluated the expression of some subtypes of T cells before and during therapy with ustekinumab and found no impact of this therapy on the levels of circulating lymphocytes expressing CD25 [19].…”
Section: Discussionmentioning
confidence: 99%
“…Economidou et al found increased baseline CD3+CD25+ T cells and a reduction in CD25 expression after treatment with cyclosporine [17]. Similarly, Langewouters et al demonstrated a significant decrease in CD4+CD25+ T cells soon after the introduction of treatment with afefacept [18]. Reddy et al evaluated the expression of some subtypes of T cells before and during therapy with ustekinumab and found no impact of this therapy on the levels of circulating lymphocytes expressing CD25 [19].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we detected CLA expressing human CD8+ T cells in the peripheral blood of the huPBL-SCID-huSkin model. The presence of CLA-expressing CD8+ T cells in the peripheral blood of psoriasis patients is a hallmark of the disease [56], [57]. Most of the huPBMC-induced changes were significantly inhibited or completely prevented after CsA and Rapamycin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Betamethasone dipropionate is a potent topical corticosteroid. In the skin, it is metabolized to its active metabolite, betamethasone (Langewouters, Bovenschen, De jong, Van Erp, & Van De Kerkhof, ; Samtani, Lohle, Grant, Nathanielsz, & Jusko, ), and betamethasone will exert anti‐inflammatory, anti‐itching, anti‐allergic and vasoconstrictive actions for a long time (Barnes, ; Barnes, ). Therefore, betamethasone dipropionate is commonly used in the treatment of psoriasis and corticosteroid‐responsive dermatoses.…”
Section: Introductionmentioning
confidence: 99%